Contemporary Oral Oncology Diagnosis and Management - Kuriakose, Moni Abraham; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This is the second of four volumes that together offer an authoritative, in-depth reference guide covering all aspects of the management of oral cancer from a multidisciplinary perspective and on the basis of a strong scientific foundation. This volume addresses a range of management issues in oral cancer, from imaging and staging through to the roles of radiation therapy and chemotherapy. Principles of ablative surgery are explained, and neck dissection and sentinel lymph node biopsy techniques, described. Detailed consideration is also given to the management of complications, salvage surgery and re-radiation, the biologic basis of treatment failure, and emerging approaches to overcome treatment resistance. The inclusion of resource-stratified guidelines will meet the needs of practitioners in different geographic regions with varying resources.
Clinical Evaluation and Staging of Oral Cancer.-Imaging of Oral Cavity Cancer -- General Principles and Management Guidelines in Oral Cavity Cancer -- Radiation Therapy in Oral Cavity Cancer -- Current and Emerging Roles of Chemotherapy in Oral Cavity Cancer -- An Overview of Ablative Surgery in Oral Cavity Cancer -- Management of the Neck in Oral Cavity Cancer -- Sentinel Lymph Node Biopsy for Early Stage Oral Cavity Cancer -- Management of Complications of Management of Oral Cancer -- Salvage Treatment for Recurrent Oral Cancer -- Understanding Therapy Failures and Emerging Approaches to Improve Outcomes -- Rare Tumors of the Oral Cavity.
Keywords: Dentistry; Medicine; Oral surgery; Maxillofacial surgery; Surgical oncology; Medicine & Public Health; Oral and Maxillofacial Surgery; Dentistry; Surgical oncology